Predictors of abdominal pain in schoolchildren: a 4-year population-based prospective study. Issue 12 (5th September 2007) - El-Metwally, A; Halder, S; Thompson, D; Macfarlane, G J; Jones, G T
Abstract : Background: Chronic abdominal pain (CAP) is common among schoolchildren, but risk factors for its onset are still largely unknown. Aims: To determine the frequency of onset of CAP in schoolchildren and investigate risk factors for its development. Methods: 1411 schoolchildren aged 11–14 years were recruited from schools in North West England. Information was collected on recent pain symptoms and potential risk factors for developing CAP. Participants were followed up 1 and 4 years later and new episodes of CAP were identified. Results: 22% reported new-onset abdominal pain at 1-year follow-up which persisted at 4-year follow-up (CAP). CAP was almost three times higher in girls than boys (34% vs 13%; χ 2 : 26.0; p<0.001). In girls, reporting headache at baseline was the only predictive factor for CAP onset: those reporting headaches experienced a doubling in the risk of symptom onset (relative risk: 2.1; 95% confidence interval: 0.95 to 4.7). In contrast, in boys, development of CAP was independently predicted by daytime tiredness (3.0; 1.2 to 7.6), lack of school enjoyment (2.0; 0.95 to 4.2), adverse psychosocial exposures (2.3; 1.2 to 4.5) and taller stature (1.9; 0.8 to 4.5). Conclusion: Our results suggest that over 20% of adolescent schoolchildren experience new-onset non-self-limiting abdominal pain over a 1-year period. Future abdominal pain is predicted by previous somatic symptom reporting in girls and both somatic symptom reporting and psychosocial factors in boys. These risk factors indicate a possible mechanism for understanding the development of CAP, and might have important implications for both primary and secondary preventive strategies.